The attenuated African swine fever vaccine HLJ/18-7GD provides protection against emerging prevalent genotype II variants in China - Zilong Wang; Jiwen Zhang; Fang Li; Zhenjiang Zhang; Weiye Chen; Xianfeng Zhang; Encheng Sun; Yuanmao Zhu; Renqiang Liu; Xijun He; Zhigao Bu; Dongming Zhao (Emerging Microbes and Infections)
Genetic changes have occurred in the genomes of prevalent African swine fever viruses (ASFVs) in the field in China, which may change their antigenic properties and result in immune escape. There is usually poor cross-protection between heterogonous isolates, and, therefore, it is important to test the cross-protection of the live attenuated ASFV vaccines against current prevalent heterogonous isolates. In this study, we evaluated the protective efficacy of the ASFV vaccine candidate HLJ/18-7GD against emerging isolates. HLJ/18-7GD provided protection against a highly virulent variant and a lower lethal isolate, both derived from genotype II Georgia07-like ASFV and isolated in 2020. HLJ/18-7GD vaccination prevented pigs from developing ASF-specific clinical signs and death, decreased viral shedding via the oral and rectal routes, and suppressed viral replication after challenges. However, HLJ/18-7GD vaccination did not provide solid cross-protection against genotype I NH/P68-like ASFV challenge in pigs. HLJ/18-7GD vaccination thus shows great promise as an alternative strategy for preventing and controlling genotype II ASFVs, but vaccines providing cross-protection against different ASFV genotypes may be needed in China.